The Role of English Language Proficiency in the Global Economy and Business Communication - Agustina, Vina; Thamrin, Nani Ronsani; Oktoma, Erwin (International Journal Administration, Business & Organization, 2024)
This research explores the role of English as a lingua franca in international business, focusing on its impact on business operations, economic communication, and cross-cultural interactions. The research objectives include understanding the relationship between English proficiency and business success, identifying common cross-cultural communication challenges, and exploring strategies to improve communication in global markets. Using a qualitative methodology, data was gathered through Semi-structured interviews conducted with 10 key informants, including 2 managers, 2 executives, and 6 employees from 2 multinational corporations and 2 small businesses that operate in global markets. Key findings indicate that higher English proficiency enhances business outcomes, while cross-cultural communication barriers often complicate international transactions. The study concludes that businesses should invest in language training to boost competitiveness and mitigate communication challenges in global operations.